2018
DOI: 10.1371/journal.pone.0193512
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the degree of antioxidant protection and the level of malondialdehyde in high-performance Polish Holstein-Friesian cows in peak of lactation

Abstract: Lipid peroxidation can be described as a process under which free radicals attack carbon double bonds of omega-3 and omega-6 fatty acids. Whereas the end products of this process are reactive aldehydes, such as malondialdehyde (MDA). Lipid peroxidation leads to adverse changes in the nutritional value of milk; therefore, higher degree of antioxidant protection (DAP) ensures higher stability of dairy products by effecting their high antioxidative potential. Therefore, the purpose of this study was to demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 28 publications
(38 reference statements)
8
41
0
Order By: Relevance
“…FFA and BHB values increased, wherease Glu values decreased in the early lactation period. Cows with higher milk production have higher MDA values in the milk [ 12 ] and may be more susceptible to lipid peroxidation owing to free radicals [ 13 , 22 ]. Therefore, the TC cows experienced NEB after parturition, and the significant positive correlation between MDA values and milk yield suggests positive relationships between the milk production, metabolism, and peripheral MDA values during the transition period.…”
Section: Discussionmentioning
confidence: 99%
“…FFA and BHB values increased, wherease Glu values decreased in the early lactation period. Cows with higher milk production have higher MDA values in the milk [ 12 ] and may be more susceptible to lipid peroxidation owing to free radicals [ 13 , 22 ]. Therefore, the TC cows experienced NEB after parturition, and the significant positive correlation between MDA values and milk yield suggests positive relationships between the milk production, metabolism, and peripheral MDA values during the transition period.…”
Section: Discussionmentioning
confidence: 99%
“…In high-yielding dairy cows, oxidative stress leads to adverse changes in the nutritional value of milk and dairy products [ 20 ]. It also has a negative impact on animal health, may cause reproductive problems and many metabolic disorders [ 11 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The determination of di-malonic aldehyde level was established using Tecan’s NanoQuant Infinite M200 PRO (Tecan Austria GmbH, Grödig, Austria) analyzer at wavelength 532 nm according to the methodology described by Kapusta et al [ 20 ]. Mean intra-assay coefficients of variation (CVs) for samples and standards were ≤2.4%, and mean inter-assay CVs were ≤2.7%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study of Mohamed Sadek () reported that the antioxidant effect of CPE in acrylamide‐intoxicated rat reflected in marked increases in GST, CAT and GSH activities and a large decrease in the MDA levels. Kapusta Kuczynska and Puppel () found that the increased lipid peroxidation leads to adverse changes in the nutritional value of milk; the highest degree of antioxidants protection was noticed in the cows with the lowest MDA content in milk. CPE could, thereby, avert lipid peroxidation and thus the formation of MDA, and cause antioxidants capacity to increase, which improves the mammary gland immune status and milk quality.…”
Section: Discussionmentioning
confidence: 99%